2007
DOI: 10.1074/jbc.m701158200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Hydroxymethyldihydropterin Pyrophosphokinase/Dihydropteroate Synthase from Arabidopsis thaliana

Abstract: In plants, 6-hydroxymethyl-7,8-dihydropterin pyrophosphokinase/7,8-dihydropteroate synthase (mitHPPK/DHPS) is a bifunctional mitochondrial enzyme, which catalyzes the first two consecutive steps of tetrahydrofolate biosynthesis. Mining the Arabidopsis genome data base has revealed a second gene encoding a protein that lacks a potential transit peptide, suggesting a cytosolic localization of the isoenzyme (cytHPPK/ DHPS). When the N-terminal part of the cytHPPK/DHPS was fused to green fluorescent protein, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…resistance at germination (Storozhenko et al, 2007;Navarrete et al, 2012). (4) Riboflavin: The Arabidopsis phs1 (PHOTOSENSITIVE1) mutant, first identified by its sensitivity to high-light stress (Ouyang et al, 2010), was found to lack a functional domain of the riboflavin biosynthesis enzyme PyrR Frelin et al, 2015).…”
Section: Modern Evidencementioning
confidence: 99%
“…resistance at germination (Storozhenko et al, 2007;Navarrete et al, 2012). (4) Riboflavin: The Arabidopsis phs1 (PHOTOSENSITIVE1) mutant, first identified by its sensitivity to high-light stress (Ouyang et al, 2010), was found to lack a functional domain of the riboflavin biosynthesis enzyme PyrR Frelin et al, 2015).…”
Section: Modern Evidencementioning
confidence: 99%
“…2A; Prabhu et al, 1997Prabhu et al, , 1998Storozhenko et al, 2007). DHPS is an enzyme that combines dihydropterin and pABA to form dihydropteroate, which is then polyglutamylated and reduced to form THF (Hanson and Gregory, 2002).…”
Section: Smx Impinges On Suc-mediated Development Through Inhibition mentioning
confidence: 99%
“…It was hypothesized that if DHPS is the true target of SMX, then elevating DHPS abundance would confer resistance to the compound. The Arabidopsis (Arabidopsis thaliana) genome contains two DHPS isoforms, one mitochondrial (At4g30000) and one cytosolic (At1g69190; Storozhenko et al, 2007); each was constitutively expressed under the control of the Cauliflower mosaic virus 35S promoter in planta. Activity of the construct was confirmed by measuring the expression of DHPS in three independently transformed lines using quantitative PCR (Supplemental Fig.…”
Section: Smx Impinges On Suc-mediated Development Through Inhibition mentioning
confidence: 99%
“…In this context, the consumption of a folate tracer with a light breakfast meal reduced bioavailability by 15 % compared with the folate tracer alone (111) . Folate bioavailability can be increased by enhancing the activity of g-glutamyl hydrolase in plants, as this would be released from the vacuole following maceration and would promote the release of unconjugated folate from the food matrix before ingestion (110) .…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%
“…The monoglutamyl: polyglutamyl folate ratio in the diet appears to have no influence on the efficiency of absorption, suggesting that the enzymic deconjugation is not a rate-limiting step (109) . However, the entrapment of folate in food matrices can influence bioavailability by rendering it inaccessible to the epithelial enzymes (110) . In this context, the consumption of a folate tracer with a light breakfast meal reduced bioavailability by 15 % compared with the folate tracer alone (111) .…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%